FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMSIA BERAT PADA IBU BERSALIN DI RS. MUHAMMADIYAH PALEMBANG TAHUN 2013 - Martina Astari Martina Astari (STIKes Budi Mulia Sriwijaya, 2015)
ABSTRACT According to the World Health Organization (WHO 2010) approximately 99% of cases of maternal deaths occur during labor and postpartum. One of the causes of maternal death due to preeclampsia. Country - developing countries maternal mortality rate of 450 / 100,000 live births, this is a very high number. In the hospital Palembang obtained Muhammaddiyah severe preeclampsia incidence by 2013 as many as 85 cases. Many things that cause severe preeclampsia include maternal age, parity, educational level, employment. The purpose of this study was to determine the relationship of maternal age, parity, educational level, work simultaneously with perinatal death. This type of research is a case control study conducted retrospectively. The population in this study were all women giving birth in hospital Muhammadiyah Palembang in the year 2013 that berjumlah2565. The study sample totaled 225 respondents. In this study conducted univariate, bivariate and multivariate analyzes. From the analysis we found no association with maternal age incidence of severe preeclampsia (P Value 0.043 OR 1.799), no parity relationship with the incidence of severe preeclampsia (P Value 0.010 OR 0.617), no correlation with the incidence rate of severe preeclampsia education (P Value 0.027 OR 1.394) , there is a relationship how to work with the incidence of severe preeclampsia (P Value 0.024 OR 0.576), the most dominant variable is the age of the mother. It is suggested to the leadership of Muhammadiyah hospital Palembang is hoped to be able to further improve health care programs for women giving birth so as to prevent the occurrence of complications during labor and to increase outreach programs about the importance of prenatal care and provide knowledge about the complications - complications during childbirth to facilitate the birth process. References : 16 (2002-2013) ABSTRAK Menurut World Health Organization (WHO 2010) sekitar 99 % kasus kematian ibu terjadi pada masa persalinan dan pasca persalinan. Salah satu penyebab kematian ibu karena preeklamsia. Dinegara – negara berkembang angka kematian ibu sebesar 450/100.000 kelahiran hidup, ini merupakan angka yang sangat tinggi. Di Rumah Sakit Muhammaddiyah Palembang didapatkan kejadian preeklamsia berat pada tahun 2013 sebanyak 85 kasus. Banyak hal yang menyebabkan preeklamsia berat diantaranya umur ibu, paritas, tingkat pendidikan, pekerjaan. Tujuan penelitian ini untuk mengetahui hubungan umur ibu, paritas, tingkat pendidikan, pekerjaan secara simultan dengan kematian perinatal. Jenis penelitian ini merupakan penelitian case control study yang dilakukan secara retrospektif. Populasi dalam penelitian ini adalah semua ibu bersalin di rumah sakit Muhammadiyah Palembang pada Tahun 2013 yang berjumlah2565. Sampel penelitian ini berjumlah 225 responden. Dalam penelitian ini dilakukan analisis univariat, bivariat dan multivariat. Dari hasil analisis didapatkan ada hubungan umur ibu dengan kejadian preeklamsia berat (P Value 0,043 OR 1,799), ada hubungan paritas dengan kejadian preeklamsia berat (P Value 0,010 OR 0,617), ada hubungan tingkat pendidikan dengan kejadian preeklamsia berat (P Value 0,027 OR 1,394), ada hubungan cara pekerjaan dengan kejadian preeklamsia berat (P Value 0,024 OR 0,576), Variabel paling dominan adalah umur ibu. Disarankan kepada pimpinan rumah sakit Muhammadiyah Palembang Diharapkan untuk dapat lebih meningkatkan program pelayanan kesehatan kepada ibu bersalin sehingga mencegah terjadinya komplikasi selama persalinan serta meningkatkan program penyuluhan tentang pentingnya pemeriksaan kehamilan dan memberikan pengetahuan mengenai komplikasi – komplikasi selama masa persalinan untuk memperlancar proses persalinan.